Associations between subjective time perception and well‐being during stressful waiting periods. (26th August 2019) - Rankin, Kyla; Sweeny, Kate; Xu, Sandra
Abstract: The passage of time is a subjective experience and can be easily distorted by concurrent emotions. Specifically, time seems to move particularly slowly when people are in a negative emotional state. The aim of the current studies was to evaluate the bidirectional relationship between subjective time perception and distress during stressful waiting periods, during which the slow passage of time may be particularly distressing. Across studies of undergraduate students awaiting a midterm exam grade (Study 1) and law graduates awaiting bar exam results (Studies 2 and 3), results revealed consistent links between distress and time perception across the waiting periods, with tentative evidence for bidirectional relationships between these experiences. That is, people who perceived time as moving slowly while they waited tended to report greater distress across the waiting period (particularly worry, anxiety, negative emotion, and poor coping), and people who reported greater distress tended to perceive time as moving more slowly. The links between distress and time perception suggest the possibility of downward spirals during stressful waiting periods, such that distress makes time seem to slow down, which then exacerbates distress. We discuss avenues for future research and potential remedies to derail the spiral of distress and time perception.